Development and Validation of a Patient-reported Score to Screen for Mucosal Inflammation in Inflammatory Bowel Disease. (24th November 2018) - de Jong, Marin J; Roosen, Danielle; Degens, Juliette H R J; van den Heuvel, Tim R A; Romberg-Camps, Marielle; Hameeteman, W; Bodelier, Alexander G L; Romanko, Igor; Lukas, Milan; Winkens, Bjorn; Markus, Tineke; Masclee, Ad A M; et al.
Abstract: Background and Aims: Patient-reported outcome measures [PROMs] assessing inflammatory bowel disease [IBD] activity are of interest for monitoring in clinical practice, telemedicine systems, or trials. Different PROMs for follow-up of disease activity are available; however, none was developed with endoscopy as gold standard. The objective of this study was to develop and validate a PROM to predict endoscopic disease activity, following the recommendations of the Food and Drug Administration. Methods: During development, 178 IBD patients undergoing a colonoscopy were asked to fill out 13 clinical questions derived from the literature. During endoscopy, inflammation was assessed with the simplified endoscopic score for Crohn's disease [CD] and the Mayo endoscopic subscore for ulcerative colitis [UC]. Based on correlation with endoscopic inflammation, questions were reduced to a total of six for CD and five for UC. The newly developed Monitor IBD At Home questionnaire [MIAH] was validated in an independent cohort of 135 CD and 131 UC patients. Additionally, diagnostic accuracy of the MIAH combined with a calprotectin home test [CHT] was assessed. Results: The MIAH-CD includes questions on rectal bleeding, mucus, stool frequency, urgency, fatigue, and patient-reported disease activity. The MIAH-UC contains items on rectal bleeding, stool frequency, urgency, abdominal pain, and patient-reported disease activity. Both questionnaires showed to be valid, reliable, and responsive to changes. The MIAH and CHT combined had a sensitivity, specificity, negative predictive value [NPV], and positive predicitive value [PPV] of 96.7%, 66.7%, 94.7%, and 76.3% for CD and of 88.2%, 81.4%, 95.6%, and 60.0% for UC, respectively, compared with endoscopy. Conclusions: The MIAH is the first PROM developed to predict endoscopic inflammation in IBD patients. A combination of this questionnaire and a CHT shows excellent diagnostic accuracy to screen for patients who need further assessment of disease activity, and can be used in daily practice, telemedicine systems, and trials.